TRANSPORT AND DEPOSITION OF REE IN H2S-RICH FLUIDS: EVIDENCE FROM ACCESSORY MINERAL ASSEMBLAGES - Gieré R. (My University, 1993)
It is shown in four examples from geologically different environments that accessory or minor minerals rich in rare-earth elements (REE) are often texturally associated with base-metal sulfides. The examples demonstrate that REE can migrate in hydrothermal fluids containing large amounts of reduced sulfur (S−II_ species, i.e. H2S, HS− and S2−. In certain fluids complexes of REE with S−II species may be important for the REE transport, but most probably only in the absence of other strong ligands such as fluoride, carbonate or possibly phosphate. Textural relationships and geochemical data suggest that the formation of REE-bearing minerals in S−II-rich environments is genetically related to the precipitation of basemetal sulfides.